2015
DOI: 10.5966/sctm.2014-0180
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Tension Regulates Human Mesenchymal Stem Cell Paracrine Functions

Abstract: The present study investigated and characterized select aspects of the human mesenchymal stem cell (hMSC) secretome and assessed its in vitro and in vivo biological bioactivity as a function of oxygen tension, specifically near anoxia (0.1% O2) and hypoxia (5% O2), conditions that reflect the environment to which MSCs are exposed during MSC-based therapies in vivo. The present study provided the first evidence of a shift of the hMSC cytokine signature induced by oxygen tension, particularly near anoxia (0.1% O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 41 publications
1
78
0
3
Order By: Relevance
“…The result of the application of MSCs was the absence of specific tubercular inflammation of the bladder caused by Mtb, which was detectable in the group without treatment (Figure , Table ). MSCs repair various injured tissues through a paracrine mechanism (Paquet et al, ; Shudo et al, ). It was shown that MSC‐derived exosomes repair the injured myocardium (Shao et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of the application of MSCs was the absence of specific tubercular inflammation of the bladder caused by Mtb, which was detectable in the group without treatment (Figure , Table ). MSCs repair various injured tissues through a paracrine mechanism (Paquet et al, ; Shudo et al, ). It was shown that MSC‐derived exosomes repair the injured myocardium (Shao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several Table 1). MSCs repair various injured tissues through a paracrine mechanism (Paquet et al, 2015;Shudo et al, 2014). It was shown that MSC-derived exosomes repair the injured myocardium (Shao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported on the capacity of MSCs to differentiate into osteogenic, chondrogenic, or adipogenic cells when cultured in hypoxic conditions [15][16][17]. However, oxygen tension may regulate human MSC paracrine functions [21], and the myocardial medium from hypoxic preconditioning can induce MSC differentiation into myocardial-like cells [33]. In our previous study, we found that a low oxygen tension induces the antiarrhythmic potential of MSCs in an animal model of myocardial infarction [24].…”
Section: Discussionmentioning
confidence: 99%
“…18,74 In line, is it shown that MSCs ageing significantly alters telomerase length, differentiation potential, proliferation index, and secretome along with the induction of a senescent phenotype in culture. 75,76 Moreover, changes in oxygen tension can modulate paracrine functions of MSCs 77 and it is likely MSC grown under variable oxygen tensions might have exosome cargo differences. Therefore, it is crucial to use MSCs at low passage, and controlled growth conditions to obtain consistent results with their exosomes.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%